Mom and me through the looking glass - Sousa, Catarina Carneiro de (2022)
This article focuses on the collaborative work of the artists CapCat Ragu and Meilo Minotaur in Metaverse environments. The aim is to describe and analyse their cooperative creative process from the perspective of one of the artists/authors, walking through three artistic works that were made in the Second Life® region of Delicatessen: ‘de Maria, de Mariana, de Madalena...’, ‘Petrified’ and ‘Meta_Body’. These projects reflect two aspects of the artists’ work – on the one hand avatar art, and on the other the creation of virtual environments. The text also reflects on the concept of shared creativity, which the artists propose through their avatar creations.